Hubungan Riwayat Asupan Zat Gizi Mikro dan Tingkat Stres dengan Penurunan Rasa Nyeri Haid - Agina, Grace; Nurhidayati, Hesti; Nasutiyon, Meliyana; Astutik, Aris Widi; Lestari, Catur Retno (Indonesian Journal of Nutrition Science and Food; Vol 2 No 2 (2023): Januari 2023, 2023)
Dysmenorrhea is an imbalance of the hormone progesterone in the blood which causes pain. The cause of pain comes from the uterine muscles, like all other muscles, the uterine muscles can contract and relax. This study aims to determine the relationship between micronutrient intake and stress levels with a decrease in menstrual pain in IVET University Semarang students during menstruation. The research methodology was taken through the informed consent, SQ-FFQ (Semi Quantitative Food Frequency Questionnaire), stress level questionnaire, and menstrual pain questionnaire with a cross-sectional approach. The population in this study were all female students at Ivet University Semarang aged 17-25 years with a sample size of 30 female students who were taken randomly. The dependent variable is dysmenorrhea while the independent variable is intake of micronutrients and stress levels. Data were tested using bivariate analysis with chi-square test to determine the relationship between intake of micronutrients and stress levels with dysmenorrhea, while multivariate analysis using multinominal logistic regression test with SPSS software. The results showed that there was "no relationship" between intake of micronutrients and stress levels with dysmenorrhea in IVET University Semarang female students.